2015
DOI: 10.5039/agraria.v10i2a5316
|View full text |Cite
|
Sign up to set email alerts
|

Bioatividade de óleos essenciais sobre Zabrotes subfasciatus Boh. (Coleoptera: Chrysomelidae) em feijão-comum armazenado

Abstract: RESUMOO presente trabalho teve como objetivo avaliar a toxicidade por fumigação, o efeito repelente, o efeito na oviposição e na emergência da geração F1 dos óleos essenciais de Croton heliotropiifolius Kunth., Croton pulegiodorus Baill., Myracrodruon urundeuva Allemão e Ocimum basilicum L. sobre Zabrotes subfasciatus, em cinco doses (0,0, 5, 10, 15 e 20 μL L -1 de ar (Coleoptera: Chrysomelidae) in common beans stored ABSTRACTThe present study aimed to evaluate the toxicity by fumigation, the repellent effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
0
9
0
4
Order By: Relevance
“…The bioactivity of essential oils (fumigant or repellent effect) obtained from Croton species on stored bean and maize pests has been recently demonstrated. Thus, for example, in kidney beans, Silva et al (2008) found that Croton grewioides Baill essential oil had a fumigant effect on adults of Z. subfasciatus, Brito et al (2015) observed that C. pulegiodorus and Croton heliotropiifolius Kunth essential oils caused 100% mortality in adults of Z. subfasciatus at all concentrations evaluated (5, 10, 15 and 20 µL L -1 air), in addition to having a repellent effect on insects; Carvalho et al (2016) observed toxicity (fumigant effect) of Croton urucurana Baill essential oil on C. maculatus, causing mortality rates greater than 80% and effects on the biology and survival of this beetle. Similarly, in maize, Magalhães et al (2015) reported that C. pulegiodorus and C. heliotropiifolius essential oils had a repellent effect and caused zero emergence of T. castaneum, while Souza et al (2016) observed that C. pulegiodorus essential oil caused mortality rates above 70% in R. dominica, when used at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bioactivity of essential oils (fumigant or repellent effect) obtained from Croton species on stored bean and maize pests has been recently demonstrated. Thus, for example, in kidney beans, Silva et al (2008) found that Croton grewioides Baill essential oil had a fumigant effect on adults of Z. subfasciatus, Brito et al (2015) observed that C. pulegiodorus and Croton heliotropiifolius Kunth essential oils caused 100% mortality in adults of Z. subfasciatus at all concentrations evaluated (5, 10, 15 and 20 µL L -1 air), in addition to having a repellent effect on insects; Carvalho et al (2016) observed toxicity (fumigant effect) of Croton urucurana Baill essential oil on C. maculatus, causing mortality rates greater than 80% and effects on the biology and survival of this beetle. Similarly, in maize, Magalhães et al (2015) reported that C. pulegiodorus and C. heliotropiifolius essential oils had a repellent effect and caused zero emergence of T. castaneum, while Souza et al (2016) observed that C. pulegiodorus essential oil caused mortality rates above 70% in R. dominica, when used at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…These studies focus mainly on the repellent or fumigant activity of essential oils and their lethal or sublethal effects. In general, the insecticidal effect of essential oils can be attributed to their chemical composition and mode of action on insects, causing them physiological changes, behavioral disorders, and mortality (CABALLERO-GALLARDO; OLIVERO-VERBEL; STASHENKO, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the potential of using essential oils as an alternative method for seed protection and control of several pests of stored products in Brazil (COITINHO et al, 2011;BRITO et al, 2015;MAGALHÃES et al, 2015;SOUZA et al, 2016;ARAÚJO et al, 2017). Essential oils present different effects on insects (SUTHISUT; FIELDS; CHANDRAPATYA, 2011; KŁYS; MALEJKY; NOWAK-CHMURA, 2017), causing biochemical, physiological, and behavioral disorders that lead to their death or affect their development and reproduction (CABALLERO-GALLARDO; OLIVERO-VERBEL; STASHENKO, 2011, CHAUBEY, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several species of the Croton genus (Euphorbiaceae) have been evaluated due to their insecticidal potential on coleoptera and lepidoptera pests of stored products (SILVA et al, 2009;SILVA et al, 2012b;CARVALHO et al, 2016). The fumigant and repellent effects of the essential oil of Croton pulegiodorus Baill were recently proven on pests of stored common bean and maize grains (BRITO et al, 2015;MAGALHÃES et al, 2015;SOUZA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%